2018
DOI: 10.1177/0888325418762050
|View full text |Cite
|
Sign up to set email alerts
|

Just a Show? Effects of Televised Debates on Political Attitudes and Preferences in Slovakia

Abstract: The popularity of televised political debates is growing, attracting millions of viewers. However, evidence that such debates can shift voters’ attitudes is mixed and the impact on voters’ preference is also mixed. In addition, the evidence comes mostly from presidential elections in the United States and almost exclusively from established democracies. A call for comparative research in new democracies has been made several times. Our research answers the call and contributes to this debate by comparing two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
1
16
0
2
Order By: Relevance
“…These results reveal that candidates’ previous notoriety influences the effects that visual cues may have on assessments of them: Televised debates may enhance the relevance of perceived personality traits over performance especially for new political contenders, who are relatively unknown to the general public. This result resonates with research showing stronger media, debate, or priming effects for lesser known candidates (Baboš and Világi 2018; Bartels 1993; Moy et al 2006; Young 2006; Zhu et al 1994). Interestingly, irrespective of mode of exposure, debate style only lowered the assessment of the least-known candidate, who was severely punished by the sharp rise in character-focused attacks in the second-round debate.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…These results reveal that candidates’ previous notoriety influences the effects that visual cues may have on assessments of them: Televised debates may enhance the relevance of perceived personality traits over performance especially for new political contenders, who are relatively unknown to the general public. This result resonates with research showing stronger media, debate, or priming effects for lesser known candidates (Baboš and Világi 2018; Bartels 1993; Moy et al 2006; Young 2006; Zhu et al 1994). Interestingly, irrespective of mode of exposure, debate style only lowered the assessment of the least-known candidate, who was severely punished by the sharp rise in character-focused attacks in the second-round debate.…”
Section: Resultssupporting
confidence: 80%
“…For instance, Pattie and Johnston's (2011) analysis of leaders' debates in the 2010 U.K. election concluded that even though party attachments and preexisting preferences affected evaluations of party leaders, debate performance was also a key factor. Also, Baboš and Világi (2018) showed that debates in Slovakia had a strong impact on opinions about the traits of previously unknown candidates, thus mirroring the findings of the U.S.-focused study by Zhu et al (1994). However, the above-mentioned literature has generally been unable to disentangle the specific effects of visual cues from the verbal and substantive information conveyed by the debates (but see Shah et al 2016).…”
Section: Debate Effects and The Role Of Exposure Modalitymentioning
confidence: 90%
See 1 more Smart Citation
“…Uten å underspille disse forskjellene, kan vi like fullt konkludere med at debatter mellom politikere på TV kan styrke den politiske kunnskapen og holdningene til politikk og samtidig påvirke seernes valg, og at de følgelig også kan oppleves som positive og oppbyggelige av de velgerne som ser på dem. Dette støttes også av funn fra andre land (Babos & Vilagi, 2018). Et gjennomgående funn er imidlertid at slike kvaliteter avhenger av en rekke faktorer, som hvor kjent kandidatene og sakene er for velgerne og hvor viktig valget oppleves.…”
Section: Tidligere Forskning Om Tv-debatterunclassified
“…Los candidatos consolidados y favoritos, principalmente cuando están en el poder, son los más reacios a aceptar los debates para no incrementar el conocimiento de sus contrincantes (Garro, 2019). Pese a la a mediatización, los debates ofrecen un espacio para la confrontación y refuerzan opiniones sobre las habilidades de liderazgo, credibilidad y competencia económica si son desconocidas previamente (Babos y Vilagi, 2018; López-García, Llorca-Abad y Valera-Ordaz, 2018).…”
Section: Introductionunclassified